Ethnic sensitivity assessment: Polatuzumab vedotin pharmacokinetics in Asian and non‐Asian patients with previously untreated diffuse large B‐cell lymphoma in POLARIX - Michael Z. Liao; Rong Deng; Leonid Gibiansky; Tong Lu; Priya Agarwal; Randall Dere; Calvin Lee; Jamie Hirata; Charles Herbaux; Gilles Salles; Chunze Li; Dale Miles (Wiley, 2023)
Abstract This ethnic sensitivity analysis used data from the phase III POLARIX study (NCT03274492) to assess polatuzumab vedotin pharmacokinetics (PKs) in Asian versus non‐Asian patients with previously untreated diffuse large B‐cell lymphoma and examined the appropriateness of extrapolating global study findings to Asian patients. PK and population PK (PopPK) analyses assessed polatuzumab vedotin analyte exposures by ethnicity (Asian [n = 84] vs. non‐Asian [n = 345] patients) and region (patients enrolled from Asia [n = 80] vs. outside Asia [n = 349]). In patients from Asia versus outside Asia, observed mean antibody‐conjugated monomethyl auristatin E (acMMAE) concentrations were comparable (1.2% lower at cycle [C]1 postdose, 4.4% higher at C4 predose; and 6.8% lower at C4 postdose in patients from Asia). Observed mean unconjugated MMAE was lower in patients from Asia by 6.5% (C1 postdose), 20.0% (C4 predose), and 15.3% (C4 postdose). In the PopPK analysis, C6 area under the curve and peak plasma concentrations were also comparable for acMMAE (6.3% and 3.0% lower in Asian vs. non‐Asian patients, respectively) and lower for unconjugated MMAE by 19.1% and 16.7%, respectively. By region, C6 mean acMMAE concentrations were similar, and C6 mean unconjugated MMAE concentrations were lower, in patients enrolled from Asia versus outside Asia, by 3.9%-7.0% and 17.3%-19.7%, respectively. In conclusion, polatuzumab vedotin PKs were similar between Asian and non‐Asian patients by ethnicity and region, suggesting PKs are not sensitive to Asian ethnicity and dose adjustments are not required in Asian patients to maintain efficacy and safety.